Enhanced Capacitive Humidity Sensing Performance at Room Temperature via Hydrogen Bonding of Cyanopyridone-Based Oligothiophene Donor - Salman Ali (MDPI AG, 2021)
Cyanopyridone-based oligothiophene donors with both hydrophobic and hydrophilic characters have been evaluated as active layers within simple capacitive devices for humidity sensing at room temperature. Surface studies using atomic force microscopy revealed a self-assembled nanofibrous network with a thin needle-like structure for the terminal hydroxy example (CP6), devoid in the methyl example (CP1). The sensing performance of each sensor was investigated over a broad range of relative humidity levels as a function of capacitance at room temperature. The sensor CP6 demonstrated favourable features such as high sensitivity (12.2 pF/%RH), quick response/recovery (13 s/20.7 s), wide working range of relative humidity (10%–95% RH), low hysteresis (0.57%), outstanding recyclability, and excellent long-term stability. From the results obtained, hydrophilicity and hydrogen bonding appear to play a vital role in enhancing humidity sensing performance, leading to possible new design directions for simple organic semiconductor-based sensors.